Sport's selection of volley-ball players: morphological and pedagogical criteria of definition of movement endowments: (information 1) - Leonid Serhiyenko; Alisa Ablikova (Kharkiv State Academy of Physical Culture, 2016)
Purpose: to define methodology of initial sports selection of young volley-ball players. Material & Methods: methods of theoretical analysis and generalization, bibliographic method of search and study of scientific information, a systematic analysis are turned to account in this work. Results: the article deals with the theoretical model of the mast important factors, which define sports endowments of volley-ball players. It is shown the point estimation of body structure and composition, motor and psychomotor abilities, dynamic possibilities, psychophisiological indices in the prognosis of volley-ball players gifted for high sports results. Conclusions: criteria of high movement endowments of volley-ball players are defined; norms of estimation of motor abilities of valley-ball players on the initial steps of sports selection are given.